2011
DOI: 10.1051/0004-6361/201016409
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in Seyfert galaxies and the unified model of AGN

Abstract: We present a deep study of the average hard X-ray spectra of Seyfert galaxies. We aim to test the unified model of active galactic nuclei, and constrain differences and similarities between different classes of objects. We analyzed all public INTEGRAL IBIS/ISGRI data available on all the 165 Seyfert galaxies detected at z < 0.2. Our final sample consists of 44 Seyfert 1s, 29 Seyfert 1.5s, 78 Seyfert 2s, and 14 narrow-line Seyfert 1s. For each subsample, we stacked all the images, and derived their average hard… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
143
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 97 publications
(101 reference statements)
25
143
3
Order By: Relevance
“…Our findings are also consistent with previous results showing low levels of reflection for high-redshift quasars (Vignali et al 1999;Reeves & Turner 2000;Page et al 2005), although we note that Ricci et al (2011) found higher levels of reflection from Seyfert2s than from Seyfert1s. Figure 8 (bottom panels) shows unobscured and obscured sources as empty and filled data points, respectively, and does not allow a firm conclusion on this point for Seyfert-like luminosity sources.…”
Section: The Reflection Componentsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are also consistent with previous results showing low levels of reflection for high-redshift quasars (Vignali et al 1999;Reeves & Turner 2000;Page et al 2005), although we note that Ricci et al (2011) found higher levels of reflection from Seyfert2s than from Seyfert1s. Figure 8 (bottom panels) shows unobscured and obscured sources as empty and filled data points, respectively, and does not allow a firm conclusion on this point for Seyfert-like luminosity sources.…”
Section: The Reflection Componentsupporting
confidence: 83%
“…Unfortunately, with our small sample, we cannot test this hypothesis at high significance. Furthermore, we must mention that local studies find mildly obscured Seyferts to have stronger or equally strong reflections than unobscured counterparts (Ricci et al 2011;Esposito & Walter 2016). We have insufficient statistics to infer a similar trend at comparable low luminosities (i.e., L log erg s 44…”
Section: The Importance Of the Reflection Componentmentioning
confidence: 99%
“…The last three observational parameters depend on the state of the accretion disk and of the presence of a gas-dusty torus on the line of sight (Awaki 1991;Cappi et al 2006;Petrucci et al 2001;Ueda et al 2007). The torus optical thickness and its geometry shape reveal themselves in the anisotropy of the absorption and scattering (Ricci et al 2011;Ueda et al 2007). Note that the photoelectric cross-section sharply declines above 20-30 keV, and have a significant influence only in soft and middle energy <2-3 keV.…”
Section: Introductionmentioning
confidence: 99%
“…This radiation can have different spectral properties depending on the geometry of the corona, its condition and state of the accretion (Beloborodov 1999;Perola et al 2002;Petrucci et al 2001;Ricci et al 2011;Vol'vach et al 2011). The presence of the gas-dust torus around the nucleus also strongly affects the absorption and emission lines.…”
Section: Introductionmentioning
confidence: 99%
“…To infer the value of the line of sight column density (N H ) we fitted the joint Swift/XRT, Chandra ACIS-S, XMM-Newton EPIC/PN and MOS, and NuSTAR FPMA and FPMB data with a model that consists of (a) an absorbed power-law with a photon index fixed to Γ=1.9, consistent with the average value of AGNs (e.g., Nandra & Pounds 1994a;Piconcelli et al 2005;Ricci et al 2011); (b) unabsorbed reprocessed X-ray emission from a slab; (c) a Gaussian to reproduce the fluorescent Fe Kα emission line (with the rest-frame energy fixed to E Kα = 6.4 keV); (d) a second power-law to reproduce the scattered component; and (e) an emission from a collisionally ionized plasma. To reproduce the effect of obscuration we included both Compton scattering and photoelectric absorption.…”
Section: Pexravmentioning
confidence: 99%